PHP 5 unleashed - Coggeshall, John, 1981- (Sams, 2005)
"PHP 5 Unleashed presents a comprehensive look at the world's most popular open-source scripting language. After covering such programming basics as functions and arrays, PHP 5 Unleashed explains how to take full advantage of many of the advanced aspects of the language, such as object-oriented programming, file system access, database interactivity, and myriad other new features introduced in PHP 5"--Jacket.